Using Ergonomic Risk Assessment Methods for Designing Inclusive Work Practices: A Case Study. Issue 3 (20th January 2016) - Hussain, Amjad; Case, Keith; Marshall, Russell; Summerskill, Steve
Abstract: In common with many industries, manufacturing faces the challenge of effective management of a diverse workforce. Humans differ greatly, but traditional manufacturing work practices do not take into account human variability issues during the work design process. Variations in individual and organizational work performance are due to many individual factors, such as age, gender, level of skill, experience, and background bring performance inconsistencies. This research investigates the effects of individual skill on work performance in general and workplace safety and human well‐being in particular. A research framework is proposed for highlighting major differences in work‐performing strategies, their potential impact on work performance, and how these findings can be used for designing more inclusive work practices. A case study has been presented in which ergonomics risk assessment methods have been used to validate the usefulness of this framework. It is also concluded that skill has a strong relationship with the level of risk attached to various task‐performing strategies.